BayanihaNets towards enabling cooperative networks - Montes, Isabel A.
The technical design of a cooperative network should be compatible with the human dynamics of voluntary cooperation for effective cooperative networking. This work presents the BayanihaNets Framework, which takes a Filipino expression for altruistic and voluntary cooperation, bayanihan, and provides design guidelines that have been built around the essential elements of bayanihan: tulungan (mutual aid) and damayan (burden-sharing). The design principle in the BayanihaNets Framework is tangible sharing, hidden mechanisms, which aims to help users recognize the bayanihan in data network sharing. Sharing can be made tangible using user interfaces and technical components that emphasize the tulungan involved in sharing one's network resources and the damayan that all users experience by participating in the cooperative network. By revealing the bayanihan in cooperative networks, users are motivated to share their network resources because they see it as an opportunity to help others to act altruistically. Bayanihan becomes both the means and the end of cooperative networks. Our design principles align well with the solutions for avoiding greed and selfishness proposed in the field of economics. There are three important factors that are needed to allow bayanihan-like sharing to be tangible: (1) minimal participation anonymity, (2) clear mutual benefits (tulungan), and (3) priority for resource owners (fair management of damayan). These factors were determined through a cooperative networking experiment that adapted the tangible sharing, invisible mechanisms design principle by introducing a social component to network resource sharing through a social networking interface that highlights how users engage in tulungan and damayan in the cooperative network. The experiment investigated how users would behave in a cooperative data capping scheme modeled after public goods games experiments when the users are made to interact through a social networking web interface. We developed cooperative networking solutions that demonstrate the effectiveness of our framework. We developed a transport layer protocol, MP-LBE, that enables tulungan by allowing concurrent multipath transport for borrowing bandwidth from one's neighbors while ensuring that damayan is managed fairly through less-than-best-effort. MP-LBE was shown to be effective in delivering observable performance gains at the application layer through a 4k video streaming experiment on a controlled test environment. Its inability to deliver LBE behavior in the wireless environment was also presented and suggested solutions were presented for implementing consistent LBE behavior. We believe these new design principles and our deeper understanding of the dynamics of resource sharing can help in the design and operation of the next generation of cooperative networks.